Cancer immunotherapy: dawn of the death of cancer?. (2nd September 2020) - Jain, Sidhant; Kumar, Sahil
Abstract: Cancer is one of the proficient evaders of the immune system which claims millions of lives every year. Developing therapeutics against cancer is extremely challenging as cancer involves aberrations in self, most of which are not detected by the immune system. Conventional therapeutics like chemotherapy, radiotherapy are not only toxic but they significantly lower the quality of life. Immunotherapy, which gained momentum in the 20 th century, is emerging as one of the alternatives to the conventional therapies and is relatively less harmful but more costly. This review explores the modern advances in an array of such therapies and try to compare them along with a limited analysis of concerns associated with them.